Students Acceptance of Mobile Final Project Guidance using Technology Acceptance Model - Kristiawan Nugroho; Sugeng Murdowo (Universitas Islam Sultan Agung, 2020)
The final project is a form of research work produced by diploma students in completing the lectures. Unfortunetly, some universities are still using manual methods in which lecturers and students, meet directly in conducting guidance, the problem is difficulty in arranging time to meet between lecturers and students especially students who have worked. The mobile system of final task guidance is developed as a solution to enable lecturers and students to communicate whenever and wherever, this research uses Technology Acceptance Model (TAM) method to analyze factors influencing the acceptance of computer application by lecturers and students, By testing technique using TAM obtained test result as follows that from F test result obtained Fcount equal to 8,805, then Fcount> Ftable (8.805> 2.42),so it can be concluded that Confidence, Hassle, Time Limitations, Usability, Ease of Use, and Behavioral Behavior jointly affect the actual usage.